2022
DOI: 10.4103/2305-0500.361221
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risks of reproductive tract infections among women of urban slums in North India

Abstract: Objective: To identify the prevalence, determinants of reproductive tract infection, and healthcare seeking behavior among ever married women of reproductive age residing in an urban slum of Faridabad, Haryana, North India. Methods: This community based cross-sectional study was conducted among ever married women aged between 15 and 49 years insured under employees state insurance scheme and residing in an urban slum of Faridabad. Simple random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A similar study from Dehradun, Uttarakhand, reported a higher proportion (63%) of respondents seeking care for RTI/STI symptoms. [ 20 ] However, a study conducted in 2019 in the urban slum of district Faridabad, Haryana,[ 21 ] found only 28.9% of the study population seeking care for RTI/STI symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar study from Dehradun, Uttarakhand, reported a higher proportion (63%) of respondents seeking care for RTI/STI symptoms. [ 20 ] However, a study conducted in 2019 in the urban slum of district Faridabad, Haryana,[ 21 ] found only 28.9% of the study population seeking care for RTI/STI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The community-based study of Phrasisombath et al . from Lao, Vientiane,[ 22 ] and other studies[ 17 21 ] conducted in India reported that vaginal discharge was the most common symptom. Though the majority of literature in this domain belongs to hospital-based studies, abnormal vaginal discharge remains the most common symptom reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations